Sharing Dissatisfaction Online: Analyzing the Nature and Predictors of Hotel Guests Negative Reviews. Issue 2 (17th February 2018) - Fernandes, Teresa; Fernandes, Filipa
ABSTRACT: Social media has expanded word of mouth (WOM) into a massive mean of online communication. Thus, consumers can now impact the reputation of a business by spreading positive or negative WOM worldwide. The hospitality industry is particularly vulnerable since the decision process is increasingly influenced by online reviews, especially about negative guests' experiences, which are considered highly valuable and helpful. However, only a few articles on online complaining behavior on the hospitality industry have been published. As such, this research aims to characterize complainers' profile and online complaints, and to determine which factors may impact them. The study analyzed 1, 191 guest reviews of hotels located in Oporto, the second largest city in Portugal (a popular Mediterranean tourism destination), listed on TripAdvisor, including 463 complaints regarding 835 incidents. Results identify dominant complaint categories and show that guest's demographics and hotel class play a critical role. The study adds to the growing body of knowledge on e-Tourism and e-Complaints and draws on relevant conclusions for both researchers and hospitality managers.